2(x-2)=5x+4-2(-6x-1)

Simple and best practice solution for 2(x-2)=5x+4-2(-6x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-2)=5x+4-2(-6x-1) equation:


Simplifying
2(x + -2) = 5x + 4 + -2(-6x + -1)

Reorder the terms:
2(-2 + x) = 5x + 4 + -2(-6x + -1)
(-2 * 2 + x * 2) = 5x + 4 + -2(-6x + -1)
(-4 + 2x) = 5x + 4 + -2(-6x + -1)

Reorder the terms:
-4 + 2x = 5x + 4 + -2(-1 + -6x)
-4 + 2x = 5x + 4 + (-1 * -2 + -6x * -2)
-4 + 2x = 5x + 4 + (2 + 12x)

Reorder the terms:
-4 + 2x = 4 + 2 + 5x + 12x

Combine like terms: 4 + 2 = 6
-4 + 2x = 6 + 5x + 12x

Combine like terms: 5x + 12x = 17x
-4 + 2x = 6 + 17x

Solving
-4 + 2x = 6 + 17x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17x' to each side of the equation.
-4 + 2x + -17x = 6 + 17x + -17x

Combine like terms: 2x + -17x = -15x
-4 + -15x = 6 + 17x + -17x

Combine like terms: 17x + -17x = 0
-4 + -15x = 6 + 0
-4 + -15x = 6

Add '4' to each side of the equation.
-4 + 4 + -15x = 6 + 4

Combine like terms: -4 + 4 = 0
0 + -15x = 6 + 4
-15x = 6 + 4

Combine like terms: 6 + 4 = 10
-15x = 10

Divide each side by '-15'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| 0.10p+0.05=20 | | 230+.15x=420 | | 2x-4=5x+4-12x-2 | | (-12.8)/(-0.8) | | 4x+2=6x-30 | | 3b+12=5b-40 | | 2/5(5w+10) | | -6(-4)-3y=39 | | x=4+13 | | 7r-5r+2r=5r-r | | 4+4r-1=7r+7-2r | | x=-21+16 | | 50=14+2x | | 4x+2=6x+30 | | -7a-15+-4a+18= | | 4v+24=-3(6v-6)+4v | | 5/4(8) | | 3(-6)+6=2(-6) | | 3p+11p=28 | | 5x-6x=8-2x | | Y=4(-5.25)+25 | | 4x+25=4 | | y/17=-11 | | 4.75=9.5-3/4x | | 9x+4=7+5x | | f/12=12/16 | | 2/3/1/13 | | Y=-3(3)+12 | | 0=9.5-3/4x | | -17/2(-20)+60 | | (a+b/c)(d-e)=f | | -17/4(-20) |

Equations solver categories